Mãos que formam laços: relações de reciprocidade na feira de orgânicos de Santiago/RS - Silva, Bernardo Rodrigues da (2018)
This dissertation looked for to understand the reciprocity relationships in the Organic Fair of the city of Santiago / RS and their respective influences on consumption habits. For this, it was searched to contextualize the organic farmers and the reason why they led them to produce and market organic; to interpret the meanings built by organic farmers in the daily life of the fair; to identify reciprocity relations in the context of the fair; and, to construct a photoetnographic narrative of the food path, from the harvest to the final consumer. Thus, four families of “organic farmers” were presented, observing points related to the cultures in which they are inserted and the relationships derived from them. The research presented a qualitative approach and was developed through several techniques of data collection, among them, interview, observation and photography are cited as primary data, and bibliographical and documentary research as secondary data. With the study, it was perceived how it was occur the historical dynamics of the organization of the fair, reaching the current marketing strategies of farmers, through the meanings built through the daily life in which these studied families are inserted, from before the fair, to the moment in consumption and relations between farmers and consumers takes form. In the first five chapters the narrative of the dissertation is presented through textual resources and in the fifth chapter it presents itself through imagery resources. All the research looked for to capture the work and relationships that occur around the food, leading the reader from the place of production and processing to the consumer, thus, the farmers presented themselves as meaning trainers through the view captured by photographic lenses.